Inovasi Pembelajaran Bahasa Jepang: Implementasi Proyek Penyusunan Buku Penunjang Tata Bahasa Tingkat Menengah Atas di Prodi Bahasa Jepang Universitas Darma Persada - Riri Hendriati; Andi Irma Sarjani; Herlina Sunarti; Hargo Saptaji (Jurnal Syntax Admiration, 2024)
This research discusses the implementation of a community service project that aims to develop a supporting book for the Grammar course for Japan language proficiency at the Senior High School Level in the Japan Language and Culture Study Program, Darma Persada University. This project was carried out from September 2023 to August 2024, involving a team consisting of four lecturers and three students. The main goal of the project is to overcome students' difficulties in understanding advanced Japan grammar by developing innovative and customized learning support books. The project methodology includes the preparation of a work plan, the collection of reference materials and the preparation of a book. The main result achieved is the preparation of supporting book modules for students in semesters 5 and 6. Despite facing time constraints, the team managed to complete the project's main target. The conclusion shows that this project has succeeded in producing learning resources that have the potential to improve the quality of advanced Japan grammar learning. The follow-up plan includes further trials and evaluations to ensure the effectiveness and usefulness of the supporting books. This project is not only beneficial to students and institutions, but also has the potential to make a positive contribution to the wider community of Japan language learners.